Ectopic lingual thyroid with vascular anomalies - Bianco, Maria Rita (Dove Medical Press, 2013)
BACKGROUND: Lingual thyroid represents 90% of ectopic thyroid tissue localizations. The first case was described by Hickman in 1869. An ectopic thyroid is often asymptomatic, but pathological or physiological conditions inducing hyperproduction of thyroid-stimulating hormone can lead an ectopic thyroid to become symptomatic. Treatment of the symptomatic ectopic thyroid can be medical, with hormone-suppressing therapy, or surgical. CASE PRESENTATION: A 17-year-old female presented to our outpatient clinic complaining of a sensation of a lump in her throat. Ear, nose, and throat (ENT) examination identified a swelling of the base of the tongue in the glossoepiglottic area. Thyroid scintigraphy showed a single contrast enhancement in the sublingual region, instead of in the normal anatomical position of the thyroid. She was treated surgically after failed hormone-suppressing therapy. An arteriography performed before the surgery showed vascular anomalies and was useful in surgical planning. CONCLUSION: Recognition of vascular anomalies in an ectopic thyroid is fundamental before surgical planning, therefore, accurate radiological study of the vasculature should always be planned before surgical treatment of this disease.